TECHNOLOGICAL APPROACH TO EDUCATION - Melikozieva Mavlyuda Abdukhafizovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article organizes all stages of education based on a technological approach, trains youth in complex thinking while providing deep and well-founded knowledge, develops students' ability to learn independently in the educational process, organizes training based on innovative technologies, activating students and students in education, technological. Based on the principles of the approach, issues of optimization of education are interpreted.